Predictive value of preoperative statistical parametric mapping of regional glucose metabolism in mesial temporal lobe epilepsy with hippocampal sclerosis - Kojan, Martin; Doležalová, Irena; Koriťáková, Eva; Mareček, Radek; Řehák, Zdeněk; Hermanová, Markéta; Brázdil, Milan; Rektor, Ivan (Epilepsy & behavior, 2018)
OBJECTIVE: This study was designed to use statistical parametric mapping of interictal positron-emission tomography using [18F]Fluorodeoxyglucose (FDG-PET) to compare the brain metabolisms of patients with mesial temporal lobe epilepsy (MTLE)/hippocampal sclerosis and controls. Another aim of this study was to analyze the potential differences among patients in terms of epilepsy duration, side of hippocampal sclerosis, histopathological findings, insult in their history, and postoperative outcomes. METHODS: We analyzed FDG-PET scans from 49 patients with MTLE/hippocampal sclerosis and 24 control subjects. We analyzed the differences in regional glucose metabolism between the patients and the control group and within the patient group using multiple variables. RESULTS: We observed widespread hypometabolism in the patient group in comparison with the control group in temporal and extratemporal areas on the epileptogenic side (ES). On the nonepileptogenic side (NES), we observed the most hypometabolism in the thalamus and the anterior and middle cingulate gyrus. In the group of patients with more severe hippocampal sclerosis, we observed statistically significant hypometabolism in the insula on the ES. In patients with poor postoperative outcomes, we found statistically significant hypometabolism in the insula on the ES and the temporal pole (TP) on the NES. Patients with any insult in their history showed hypermetabolism in the TP on both sides. CONCLUSION: Our study showed that there are widespread changes in metabolism in patients with MTLE in comparison to controls, either inside or outside the temporal lobe. There are significant differences among these patients in terms of postoperative outcomes, degree of hippocampal sclerosis, and insults in their history.
Keywords: Fluorodeoxyglucose F18; mozek; Humans; Case-Control Studies; lidé středního věku; studie případů a kontrol; Predictive Value of Tests; epilepsie temporálního laloku; Postoperative Period; Female; mladý dospělý; dospělí; fluorodeoxyglukosa F18; Temporal Lobe; spánkový lalok; Hippocampus; lidé; hipokampus; mozková kůra; glukosa; Cerebral Cortex; Adult; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; Brain; Glucose; Epilepsy, Temporal Lobe; skleróza; Positron-Emission Tomography; Young Adult; mužské pohlaví; pooperační období; Sclerosis; pozitronová emisní tomografie